Evaluation of anti-inflammatory activity of ethanolic extract of Cananga odorata Lam in experimental animals - Maniyar, Yasmeen A.; Devi, C. H. Janaki (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The current study evaluates the anti-inflammatory activity of ethanolic extract of Cananga odorata Lam (EECO) in experimental animals. Methods: Acute toxicity test was done following OECD guidelines. Carrageenan induced paw edema method in Wistar Albino rats were used in this study. Aspirin in the dose of 300 mg/kg was used as the standard drug and three doses of EECO (100 mg/kg, 200 mg/kg and 400 mg/kg b.w. p.o) were used as the test drug. The results were measured at 1st hr, 3rd hr and 5th hr after carrageenan injection. Results: EECO in the doses of 100 mg/kg, 200 mg/kg and 400 mg/kg showed highly significant anti-inflammatory activity (p<0.001) (p<0.001) (p<0.001) at 3rd hr and (p<0.001) (p<0.001) (p<0.001) 5th hr, respectively. In doses of 100 mg/kg, 200 mg/kg, and 400 mg/kg of EECO showed the percentage of inhibition of 62.9% which is more than the standard drug aspirin, which showed 60.14% inhibition. Conclusion: EECO has significant anti-inflammatory activity.